2015
DOI: 10.3906/biy-1412-37
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon sources on growth and GC-MS basedmetabolite profiling of Arnica montana L. hairy roots

Abstract: Arnica montana L. (Asteraceae) is an economically important herb that contains numerous valuable biologically active compounds accumulated in various parts of the plant. The effects of carbon sources (sucrose, maltose, and glucose) at different concentrations (1%, 3%, 5%, 7%, and 9%) on growth were studied and GC-MS based metabolite profiling of A. montana hairy roots was conducted. The optimal growth and biomass accumulation of transformed roots were observed on an MS nutrient medium containing 3% or 5% sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…According to Chen et al [ 57 ], initial sucrose concentration had a significant influence on the growth of transformed cell cultures of S. miltiorrhiza , showing the fastest growth in medium containing 30 g/L sucrose. This concentration was reported to be the best for Arnica montana hairy root growth by Petrova et al [ 58 ] The similar value of sucrose (30 g/L) obtained in this study was found to promote the biomass production of S. corrugata hairy roots ( Figure S5 , Supplementary Materials ). This result is consistent with other literature studies.…”
Section: Discussionsupporting
confidence: 86%
“…According to Chen et al [ 57 ], initial sucrose concentration had a significant influence on the growth of transformed cell cultures of S. miltiorrhiza , showing the fastest growth in medium containing 30 g/L sucrose. This concentration was reported to be the best for Arnica montana hairy root growth by Petrova et al [ 58 ] The similar value of sucrose (30 g/L) obtained in this study was found to promote the biomass production of S. corrugata hairy roots ( Figure S5 , Supplementary Materials ). This result is consistent with other literature studies.…”
Section: Discussionsupporting
confidence: 86%
“…Contrastingly, studies performed in the hairy roots of Arnica montana exposed that the optimal growth and biomass accumulation occurred in MS at 3 % or 5 % sucrose, whereas GC‐MS analysis sustained that sugars and sugar alcohols were influenced by the concentration of the respective carbon sources in the culture medium. Simultaneously, the levels of secondary metabolites were not markedly modified [15] . On the other hand, the hairy roots of Mentha spicata improved their levels of phenolic acids and biomass by the addition of 0.3 mg ⋅ L −1 indole‐3‐butyric acid (IBA) and 100 μM methyl jasmonate (MeJA) [16] .…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the levels of secondary metabolites were not markedly modified. [15] On the other hand, the hairy roots of Mentha spicata improved their levels of phenolic acids and biomass by the addition of 0.3 mg • L À 1 indole-3-butyric acid (IBA) and 100 μM methyl jasmonate (MeJA). [16] Interestingly, the metabolic profiling of hairy roots from M. spicata raised from the infection of two different strains of A. rhizogenes (A13 and Mean 58.4 [b] 37.3 [c] 40.2 [c] 62.9 [b] 38.0 [c] 35.6 [c] 108 [a] 33.8 [c] 102 [a] 94.5 R318) had substantial divergences.…”
Section: Chemical Screening Of Ten Hairy Roots Randomly Chosenmentioning
confidence: 99%
“…In this work, different kinds, and concentrations of auxin and cytokinin on the foliar explants of A. montana plantlets influenced callus or root formation, percentage induction, and phenotypic characteristics, results that agree with those of previous studies on A. montana. In the apical shoots, cotyledons, hypocotyls, leaves, and petioles of A. montana, low concentrations of 2,4-D promote callus induction, while high concentrations cause callus necrosis [22,29,30]. Callus growth was inhibited during the second phase, adding only 2,4-D, but combining 2,4-D with BAP re-established biomass growth [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, reports about the in vitro plant cultures of A. montana to produce SMs are scarce. The hairy root of this species produces thymol derivatives, flavones (chrysin), and phenolic acids (2-phenyl lactic, m-hydroxybenzoic, protocatechuic, 4-hydroxyphenyllactic, and caffeic acids) [21,22]. There are no reports about A. montana cell suspension culture producers of SMs, and to develop it is imperative since there was previously a significant increase in the concentration of outstanding bioactive SMs compared to wild plants: range values of 0.31% to 1.10% of total content of sesquiterpene lactones, 1.44% to 2.44% of total content of phenolic acids, and 0.6% to 1.7% of total content of flavonoids, determined in the flowers, which are the organ with the highest production of these three types of SMs in wild plants [4,23,24].…”
Section: Introductionmentioning
confidence: 99%